Three dimensional porous Hofmann clathrate [MIIPtII(CN)4]∞ (M = Co, Ni) synthesized by using postsynthetic reductive elimination. Issue 48 (2nd June 2017) - Okamura, Takuro; Wu, Bin; Iguchi, Hiroaki; Breedlove, Brian K.; Yamashita, Masahiro; Kosaka, Wataru; Miyasaka, Hitoshi; Takaishi, Shinya
Abstract : We synthesized cyano-bridged three dimensional metal–organic frameworks [M II (H2 O)2 Pt IV (CN)4 Br2 ]∞ · n (H2 O) (1 : M = Co, 2 : M = Ni) with an NbO type topology. Abstract : We synthesized cyano-bridged three dimensional metal–organic frameworks [M II (H2 O)2 Pt IV (CN)4 Br2 ]∞ · n (H2 O) (1 : M = Co, 2 : M = Ni) with an NbO type topology. Although1 and2 have no accessible pores, these MOFs were found to undergo reductive elimination of the axial bromides on the Pt IV ions as well as removal of water molecules upon heating to form porous [M II Pt II (CN)4 ]∞ (1′ : M = Co, 2′ : M = Ni) with retention of their crystallinity.